Nurturing consciousness for mobilization: Dynamics of land rights movements in Nepal - Gurung, Ram (Journal of Nepalese Studies, 2024)
Conscious participant(s) is crucial in the organization and mobilization of social movements. It mediates the entire process of movement practices. Despite its importance, it is regarded merely as an autonomous internal dynamic, overlooking the role external factors play in building consciousness among marginalized communities. In-depth conversations with movement participants and activists in Nepal’s land rights movements, evident that nurturing consciousness is a process predominantly shaped by external factors, particularly the individual and organizations. To transform marginalized communities’ everyday experiences into collective realizations, external actors and organizations facilitate marginalized people to become conscious with the use of prevalent approaches and replicated strategies. Nepal’s land rights movements provide insights: movement organization’s internal efforts are necessary but not sufficient. For influential organizations of movements, marginalized communities adopt external national and international influences to convert their experiences into conscious and influential mobilization.